Keunikan Empat Karya Musik Kontemporer pada Gelaran Seremonialita Javid Nama Tanaka Manalu - Wiflihani Wiflihani (Gondang: Jurnal Seni dan Budaya, 2017)
Contemporary music emerges as a contemporary development in the journey of the art of music. Contemporary is regarded as a way to respond to the present, or the latest cultivation pattern or also one of the working attitude of art that is involved. Although later, the development of contemporary music that many raises questions about the existence of contemporary music in Indonesia. Contemporary music is increasingly pervasive and spreads unstoppable among the contemporary definition of bergamnya itself. In a celebration performed by young people of Medan, by presenting the work of music in accordance with their perspective. It seems clear that contemporary terminology is not able to stem the desire to work of the young generation, which shows a side that is still related to the culture of the country itself and still describes the characteristics of Indonesian culture.